DWT-Based Islanding Detection Method for DFIG-typed WTs - Yılmaz, Alper; Bayrak, Gökay (Institute of Electrical and Electronics Engineers Inc., 2020)
In this study, it is aimed to image the transparent objects by applying the phase shifting technique to lateral shearing digital holographic microscopy. In order to extract the phase information from interference patterns obtained by phase shifting technique, a hologram with 4 different phase values is created using quarter wave and half wave plates. In conventional lateral shearing digital holographic microscopy, duplicate images are formed due to the interference between two sheared object beams and information overlap occurs. The aim is to eliminate this problem by shifting the phase. Thus, the noise-free image is reconstructed without the need for any special signal processing algorithm or filter design. In this study, the images obtained with the conventional method and the proposed system are presented in 3 dimension. By comparing these two images, it is proved that the result is successfully achieved with the proposed system. © 2020 IEEE.
CBAG Kullanan Ruzgar Turbinlerinde Ada Mod Calmann ADD Yontemi ile Tespiti
28th Signal Processing and Communications Applications Conference, SIU 2020 -- 5 October 2020 through 7 October 2020 -- -- 166413
Keywords: digital holographic microscopy; lateral shearing; phase shifting; transparent object.